Intratendinous Strain Variations of the Supraspinatus Tendon Depending on Repair Technique: A Biomechanical Analysis Regarding the Cause of Medial Cuff Failure. Issue 7 (June 2021) - Hackl, Michael; Nacov, Julia; Kammerlohr, Sandra; Staat, Manfred; Buess, Eduard; Leschinger, Tim; Müller, Lars P.; Wegmann, Kilian
Background: Double-row (DR) and transosseous-equivalent (TOE) techniques for rotator cuff repair offer more stability and promote better tendon healing compared with single-row (SR) repairs and are preferred by many surgeons. However, they can lead to more disastrous retear patterns with failure at the medial anchor row or the musculotendinous junction. The biomechanics of medial cuff failure have not been thoroughly investigated thus far. Purpose: To investigate the intratendinous strain distribution within the supraspinatus tendon depending on repair technique. Study Design: Controlled laboratory study. Methods: Twelve fresh-frozen cadaveric shoulders were used. The intratendinous strain within the supraspinatus tendon was analyzed in 2 regions—(1) at the footprint at the greater tuberosity and (2) medial to the footprint up to the musculotendinous junction—using a high-resolution 3-dimensional camera system. Testing was performed at submaximal loads of 40 N, 60 N, and 80 N for intact tendons, after SR repair, after DR repair, and after TOE repair. Results: The tendon strain of the SR group differed significantly in both regions from that of the intact tendons and the TOE group at 40 N ( P ≤ .043) and from the intact tendons, the DR group, and the TOE group at 60 N and 80 N ( P ≤ .048). SR repairs showed more tendon elongation at the footprint and less elongation medial to the footprint. DR and TOE repairs did not provide significant differences in tendon strain when compared with the intact tendons. However, the increase in tendon strain medial to the footprint from 40 N to 80 N was significantly more pronounced in the DR and TOE group ( P ≤ .029). Conclusion: While DR and TOE repair techniques more closely reproduced the strains of the supraspinatus tendon than did SR repair in a cadaveric model, they showed a significantly increased tendon strain at the musculotendinous junction with higher loads in comparison with the intact tendon. Clinical Relevance: DR and TOE rotator cuff reconstructions lead to a more anatomic tendon repair. However, their use has to be carefully evaluated whenever tendon quality is diminished, as they lead to a more drastic increase in tendon strain medial to the footprint, putting these repairs at risk of medial cuff failure.